The effect of rising concentration of atmospheric carbone dioxide on crop production - Tamás, András (Acta Agraria Debreceniensis, 2016)
In the atmosphere, the amount of carbon dioxide and other greenhouse gases are rising in gradually increasing pace since the Industrial Revolution. The rising concentration of atmospheric carbon dioxide (CO2) contributes to global warming, and the changes affect to both the precipitation and the evaporation quantity. Moreover, the concentration of carbon dioxide directly affects the productivity and physiology of plants. The effect of temperature changes on plants is still controversial, although studies have been widely conducted. The C4-type plants react better in this respect than the C3-type plants. However, the C3-type plants respond more richer for the increase of atmospheric carbon dioxide and climate change.